Copper Brace Method: A New Technique for Reconstructing Broken Bone Fragments - Jayaprakash, Paul T.; Alarmebnangai, S.; Hadi, Helmi (2017)
Human skulls and other bones recovered in forensic anthropological contexts may be found broken into multiple pieces, requiring reconstruction. This article prescribes a new method, termed copper-brace met hod, that simultaneously enables retaining the matching pieces of bones and readjusting them during the process of reconstruct ion, ensuring an acceptable likeness in the spatial and contour configuration of the final reconstruction.